Economic Environment Activities of Russian Corporations - Sozinova, Anastasiya A.; Zhelnina, Evgenia V.; Prokhorova, Victoria V.; Zelinskaya, Maria V.; Putilina, Irina N. (International Journal of Economics and Financial Issues, 2016)
The article investigates the activity of enterprise structures in the conditions of the external environment, which includes both the legislative provision, as well as the macroeconomic situation. In particular, the Corporation, in its current activities are guided by the following key indicators: the dynamics of the exchange rate; the level of market prices for manufactured products; the dynamics of stock indices of activity; the level of bank lending rates; the tax environment; dynamics and structure of investment. Centrifugal forces led to the collapse of confidence monopolized and centralized organization of the economy; encouraged independence and allowed rental companies prompted the director’s body to their gradual subordination of groups of employees, shares the position of the heads, ie corporatism acquired hue loyalty authorities. The tension in the foreign exchange market, along with the complete absence of corporate securities market make the regional financial instruments are virtually the only way to protect against inflation and income in Russia. We consider the general financial condition of Russian companies, which can be characterized by summary measures according to State Statistics Committee of Russia. Keywords: macroeconomic situation, Russian corporations, economic environment. JEL Classifications: E21, O13